2015
DOI: 10.1111/jgs.13389
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Activities of Daily Living After a Visit to a Canadian Emergency Department for Minor Injuries in Independent Older Adults: Are Frail Older Adults with Cognitive Impairment at Greater Risk?

Abstract: Easy-to-administer frailty and cognitive screening tools should be included in ED assessments to identify independent older adults at high risk of functional decline after minor injury so that appropriate services may be provided to prevent deterioration in ADLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…The second new outcome was disease-specific; namely that living with dementia and diabetes increased the risk for severe hypoglycemia compared with persons living with diabetes and without dementia (Abbatecola et al , 2015; Prinz et al , 2015). Fourteen new articles (Chang et al , 2012; Chen et al , 2014; Huijts et al , 2013; Llibre et al , 2014; Katsoulis et al , 2014; Lee et al , 2015; Mignardot et al , 2014; Murao et al , 2014; O’Donnell et al , 2012; Park et al , 2016; Sanyal et al , 2014; Warchol-Celinska et al , 2015; van Asch et al , 2013) fell into existing chronic condition-outcome pairings and did not change the quality or strength of the evidence, and four articles (Hawkins et al , 2012; Jacobs et al , 2012; Hajduk et al , 2013; Provencher et al , 2015) were found in separate areas where there was previously no evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The second new outcome was disease-specific; namely that living with dementia and diabetes increased the risk for severe hypoglycemia compared with persons living with diabetes and without dementia (Abbatecola et al , 2015; Prinz et al , 2015). Fourteen new articles (Chang et al , 2012; Chen et al , 2014; Huijts et al , 2013; Llibre et al , 2014; Katsoulis et al , 2014; Lee et al , 2015; Mignardot et al , 2014; Murao et al , 2014; O’Donnell et al , 2012; Park et al , 2016; Sanyal et al , 2014; Warchol-Celinska et al , 2015; van Asch et al , 2013) fell into existing chronic condition-outcome pairings and did not change the quality or strength of the evidence, and four articles (Hawkins et al , 2012; Jacobs et al , 2012; Hajduk et al , 2013; Provencher et al , 2015) were found in separate areas where there was previously no evidence.…”
Section: Resultsmentioning
confidence: 99%
“…13,15 These studies, however, were limited by the absence of suitable comparison groups and by retrospective reports of pre-illness function. In contrast, our study included a matched comparison group of older persons with no ED visit and included prospective reports of pre-illness function.…”
Section: Discussionmentioning
confidence: 99%
“…24 Using similar inclusion criteria, Provencher et al demonstrated that the risk of functional decline at 3 and 6 months after an emergency department visit was significantly greater for frail participants with cognitive impairment than non-frail participants without cognitive impairment. 25 Shapiro and colleagues demonstrated that 3 months after an emergency department visit for a minor traumatic injury, 7% and 23% of patients had a decline in basic and instrumental activities of daily living, respectively. 26 …”
Section: Discussionmentioning
confidence: 99%